A Pilot Study Investigating the Influence of Glucagon-Like Peptide-1 Receptor Single Nucleotide Polymorphisms on Gastric Emptying Rate in Caucasian Men - Yau, Adora M. W.; McLaughlin, John; Maughan, Ronald J.; Gilmore, William; Ashworth, Jason J.; Evans, Gethin H. (Frontiers in Physiology, 2018)
Gastric emptying rate in humans is subject to large individual variability, but previous research on the influence of genetics is scarce. Variation in the glucagon-like peptide-1 receptor (GLP1R) gene is a plausible candidate gene to partially explain the high variance. This study aimed to investigate the influence of genetic variation in the GLP1R gene on gastric emptying rate of a glucose solution in humans. Forty eight healthy Caucasian males took part in this investigation. Gastric emptying rate of a 6% glucose solution was assessed using the 13C breath test method and a venous blood sample was obtained from each participant. Participants were genotyped for 27 Tag single nucleotide polymorphisms (SNPs) in the GLP1R locus using Sequenom MassARRAY iPLEX GOLD analysis and MALDI-TOF mass spectrometry. The time at which maximal emptying rate occurred (Tlag) was faster in participants with the CC genotype than in TT and TC genotypes for SNP rs742764: [median (quartiles) CC, 35 (30–36) min vs. TT, 43 (39–46) min, and TC, 41 (39–45) min; P < 0.01]. Tlag was also slower in participants with the AA genotype compared to the TT and TA genotypes for SNP rs2254336: [AA, 43 (39–49) min vs. TT, 36 (34–41) min, and TA, 39 (35–42) min; P < 0.05]. Analysis by phenotype also showed differences in half-emptying time (T12) and Tlag for SNPs rs9283907, rs2268657, and rs2254336. Several neighboring Tag SNPs within the GLP1R gene were found to be associated with gastric emptying rate, and should be further investigated.